Effects of local microstructure on crack initiation in super martensitic stainless steel under very-high-cycle fatigue. (October 2022) - Li, Xue; Dai, Yajun; Wang, Xiangyu; Liu, Yongjie; Chen, Yao; Wang, Chong; Zhang, Hong; Li, Lang; Liu, Hanqing; He, Chao; Wang, Qingyuan
Highlights: Crack initiation from the microstructural inhomogeneity was investigated in very high cycle fatigue. Mode II cracking along the martensite lath dominant the crack initiation behavior. Fatigue cracking prefers to occur at the boundaries of favorably oriented martensite lath due to slip-cracking process. Abstract: Super martensitic stainless steel is known for its outstanding mechanical properties, which lead to its widely application in structural component bearing cyclic loadings. This study investigates the effect of local microstructure on the crack initiation behavior of a super martensitic stainless steel in the very high cycle fatigue (VHCF) regime. Results show that the non-inclusion-induced crack initiation is the dominating pattern of VHCF failure. Fatigue cracks initiate from the boundaries of the martensite lath due to the mode II cracking process, resulting in the formation of a slip area located at the core of the fine granular area (FGA). The size and the orientation of the martensite lath determine the morphology of the slip area but exert limited influence on the formation of the FGA at the fracture surface. These results may effectively improve the service safety and reliability of super martensitic stainless steel.